METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KECERDASAN INTELEKTUAL DAN SPIRITUAL DI SMK TAKHASSUS AL-QUR’AN - Ma’ruf, Muhammad; Muntaqo, Rifqi; El Syam, Robingun Suyud (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2025)
The research focuses on Islamic religious education learning methods to improve the intellectual and spiritual intelligence of students at the Takhassus Al-Qur'an Vocational School. This research is a qualitative study using a case study approach. Data were collected in a natural setting as a direct source of data, namely from Islamic Religious Education teachers, and then analyzed descriptively. The findings show that the learning methods used in Islamic religious education at SMK Takhassus Al-Qur'an are highly varied, including: inquiry learning, discovery learning, nature contemplation, assignments, discussions, gallery walks, and practical work. This diversity has resulted in improving students' intellectual intelligence. This success is reflected in the students' increased ability to read, memorize, and analyze various materials presented by the teacher. Although the process encountered several obstacles that prevented this improvement from proceeding as expected by the teacher, the variety of learning methods has produced students with good spiritual intelligence. This is indicated by students' polite behavior towards teachers, staff, and their peers. This increase in spiritual intelligence does not arise solely from the Islamic religious education learning process. Rather, it is the accumulation of learning methods that foster understanding and a school environment that supports the development of spiritual intelligence.